Community-Based Bayesian Aggregation Models for Crowdsourcing - Venanzi, Matteo; Guiver, John; Kazai, Gabriella; Kohli, Pushmeet; Shokouhi, Milad (WWW '14 Proceedings of the 23rd international conference on World wide web, 2014)
This paper addresses the problem of extracting accurate labels from crowdsourced datasets, a key challenge in crowdsourcing. Prior work has focused on modeling the reliability of individual workers, for instance, by way of confusion matrices, and using these latent traits to estimate the true labels more accurately. However, this strategy becomes ineﬀective when there are too few labels per worker to reliably estimate their quality. To mitigate this issue, we propose a novel community-based Bayesian label aggregation model, CommunityBCC, which assumes that crowd workers conform to a few diﬀerent types, where each type represents a group of workers with similar confusion matrices. We assume that each worker belongs to a certain community, where the worker’s confusion matrix is similar to (a perturbation of) the community’s confusion matrix. Our model can then learn a set of key latent features: (i) the confusion matrix of each community, (ii) the community membership of each user, and (iii) the aggregated label of each item. We compare the performance of our model against established aggregation methods on a number of large-scale, real-world crowdsourcing datasets. Our experimental results show that our CommunityBCC model consistently outperforms state-of-the-art label aggregation methods, gaining, on average, 8% more accuracy with the same amount of labels.
Best paper runner up